Two-step widefield fundus fluorescein angiography-assisted laser photocoagulation in pediatric retinal vasculopathy: A pilot study - Peng, Jie; Ren, Jianing; Zhang, Xuerui; Yang, Yuan; Zou, Yihua; Xiao, Haodong; Xu, Yu; Zhao, Peiquan (Frontiers in Medicine, 2022)
Purpose To introduce the procedures of two-step fundus fluorescein angiography (FFA) and evaluate its utility in the management of pediatric retinal vasculopathy. Materials and methods In this retrospective study, medical records of 12 patients who received two-step FFA were studied. The two-step FFA consisted of step 1 [low-dose (LD)] FFA at an intravenous dose of 1.5 mg/kg fluorescein, followed by step 2 [reduced dose (RD)] FFA at a dose of 6.2 mg/kg fluorescein. Demographic data, including age, gender, diagnosis, weight, gestational age, birth weight, and weight on the examination day were taken, were collected. The results of two-step FFA and treatment were recorded. Results A total of 20 eyes were studied. The top 5 common FFA changes in RD-FFA included peripheral avascular zone (15 eyes), fluorescein leakage (10 eyes), supernumerous vascular branching (10 eyes), neovascularization (NV) (8 eyes), and absence of the foveal avascular zone (6 eyes). LD-FFA was efficient to show all the NV without severe vitreous dye in 8/8 (100.0%) eyes with NV, partial peripheral avascular zone in 11/15 (73.3%) eyes, while RD-FFA always offered more information in all the eyes. Thirteen eyes had laser photocoagulation under the guidance of LD-FFA. In 4 (30.8%) eyes, RD-FFA revealed more lesions and an immediate relaser was performed. Laser photocoagulation was successfully performed in all the 13 eyes in one session without being rearranged. After a median follow-up of 28.1 months, all the eyes were in a stable status. Conclusion Step-one LD-FFA acted as a pre-FFA to show the NV, and step-two RD-FFA acted as a double-check. The modified strategy may be a helpful clinical adjuvant in the laser photocoagulation of pediatric retinal disorders, especially for young ophthalmologists.